Review of the genus Aschistophleps Hampson, 1893 (Lepidoptera, Sesiidae) of Laos - Gorbunov, Oleg G. (Zootaxa, 2021)
The genus Aschistophleps Hampson, 1893 is reviewed for Laos. A. longipoda Arita & O. Gorbunov, 2000 is reported for the country for the first time. Two new species A. zamesovi sp. nov. and A. nahinensis sp. nov. are described and figured. The mud-puddling behaviour of males of these species are discussed. All material, including the types of new described species are deposited in the collection of the A.N. Severtsov Institute for Ecology and Evolution, Russian Academy of Sciences, Moscow, Russia (COGM).